2011
DOI: 10.1111/j.1365-2494.2011.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasture use and management strategies in the Ankole pastoral system in Uganda

Abstract: The Bahima ethnic group have been crossbreeding autochthonous Ankole with Holstein-Friesian cattle. Separate herds (pure Ankole and crossbreds) are common. A survey was conducted to characterize pasture utilization and management in the Ankole region to gain a better understanding of current and emerging practices. Herds are largely grazed by continuous stocking although there are efforts to establish paddocks. Factors considered for pasture allocation to cattle genotypes were high-quality feed, limited shrubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Grasslands of East Africa, particularly in Ethiopia, support one of the highest livestock populations in Africa (FAO, ). However, the productivity of the grazing livestock in the region has remained low, mainly due to the critical feed shortages and inadequate quality of the pasture on offer, resulting from poor management, overgrazing and recurrent droughts (Coppock, ; Solomon et al ., ; Roschinsky et al ., ). The low digestibility and crude protein (CP) contents of such forages have been reported to limit dry‐matter and energy intakes (Schlecht et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Grasslands of East Africa, particularly in Ethiopia, support one of the highest livestock populations in Africa (FAO, ). However, the productivity of the grazing livestock in the region has remained low, mainly due to the critical feed shortages and inadequate quality of the pasture on offer, resulting from poor management, overgrazing and recurrent droughts (Coppock, ; Solomon et al ., ; Roschinsky et al ., ). The low digestibility and crude protein (CP) contents of such forages have been reported to limit dry‐matter and energy intakes (Schlecht et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In the northern region of Uganda where pastoralism is dominant, the natural pastures such as giant thatching grass [Hyparrhenia rufa (Nees) Stapf], Urochloa spp., red oat grass (Themeda triandra Forssk.) and Rhodes grass (Chloris gayana Kunth), are preferred pasture species for standing hay (Roschinsky et al, 2012). A review of reports from Kenya, Uganda, and Rwanda indicated that the common methods of hay making are loose hay (53%), box baling (47%), and machine baling (6%) (Lukuyu et al, 2013).…”
Section: Hay Makingmentioning
confidence: 99%
“…Drought and heat-induced livestock mortality has increased in Uganda due to starvation and lack of water; this causes significant economic losses, and negatively impacts on livelihoods of pastoral communities and increases their impoverishment (Stites et al 2010, Mwaura andKatunze 2014). Increased bush expansion in Ugandan rangelands by several native species, including Acacia (Vachellia) hockii De Wild and Lantana camara L., and increasing non-palatable grass species such as Cymbopogon afronardus Stapf have contributed to a decline in rangeland productivity, especially for grazers (Mugasi et al 2000, Oba et al 2008, Roschinsky et al 2012. We posit that many of these aforementioned challenges can be traced back to land use and economic policies originating from the colonial era, which generally focused on the production efficiency of a small number of provisioning ecosystem services and failed to account for regulatory, cultural and supporting ecosystem services from rangelands (Muhereza 2001, Pulkol 1994, Kisamba-Mugerwa 1992.…”
Section: Introductionmentioning
confidence: 99%